Bases do ensino de oncologia. - J L da Ascensão (Acta Médica Portuguesa, 1994)
We define the parameters for preclinical and postgraduate teaching in oncology coupled with hematology with a view to train competent physicians in these areas as well as to encourage a restructuring of the health system to permit optimal delivery of care to all people. We analyze and define curricular changes in the medical schools to be implemented at a national level with the introduction of an intensive course in hematology-oncology during the clinical clerkships. This course would require a host of appropriate teachers, continued monitoring and a final appropriate written exam. The Oncologic training of the medical student requires an interdisciplinary approach with an emphasis on the personalized approach to the patient with cancer. The postgraduate training should follow minimal guidelines established by the ESMO, EORTC and ABIM with an emphasis on combined training in oncology/hematology, following appropriate training in internal medicine. A need for continued "recycling" of generalists in oncology is felt to be important. Other issues discussed include: methods of teaching and their evaluation; the career pathway for the scientist (docent) in oncology; preventive medicine and finally the need for continuing medical education. An evaluation of the quality of medicine and of ethical and professional conduct while not specifically linked to oncology is considered a vital part of medical care and needs to be placed in perspective.